2018
DOI: 10.18502/pbr.v4i2.215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lavender aromatherapy on well-being among hemodialysis patients: A randomized clinical trial

Abstract: In spite of the improvement of dialysis techniques, hemodialysis patients still experience debilitation. Impaired functioning, well-being, and quality of life are among the factors that are of a great concern in these patients. The current study aimed to examine the effects of lavender essential oil on well-being among hemodialysis patients. This randomized clinical trial was conducted on 30 hemodialysis patients. For each patient in the experimental group, five cotton balls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, a study reported that aromatherapy with lavender essential oil had no significant effect on sleep quality in patients undergoing maintenance hemodialysis (21). Another study revealed that aromatherapy with lavender essential oil in concentrations of 40 -50% could positively affect the well-being of patients undergoing maintenance hemodialysis (22). Our review found inconclusive results on lavender aromatherapy's effect on hemodialysis patients' sleep quality and well-being.…”
Section: Introductionmentioning
confidence: 64%
“…However, a study reported that aromatherapy with lavender essential oil had no significant effect on sleep quality in patients undergoing maintenance hemodialysis (21). Another study revealed that aromatherapy with lavender essential oil in concentrations of 40 -50% could positively affect the well-being of patients undergoing maintenance hemodialysis (22). Our review found inconclusive results on lavender aromatherapy's effect on hemodialysis patients' sleep quality and well-being.…”
Section: Introductionmentioning
confidence: 64%
“…Stimulation of the trigeminal nerves on the tip of the nose can produce warming or cooling sensations [12]. The previous research indicated lavender aromatherapy was effective to reduce anxiety, fatigue, depression, pain, and improve psychological well-being and mood among patients undergoing hemodialysis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Linalool juga memiliki sifat spasmolitik (dapat merelaksasi otot polos pada saluran pencernaan) yang dapat menurunkan rasa mual (Caroline, 2022). Selain itu, menurut beberapa penelitian, aromaterapi lavender efektif digunakan untuk meningkatkan kualitas tidur, meringankan gejala kelelahan, dan meningkatkan persepsi terkait kualitas hidup pada pasien yang menjalani prosedur hemodialisa (Nesami et al, 2018). Aromaterapi juga bisa dikombinasikan dengan terapi komplementer lainnya seperti foot massage untuk memberikan efek rileks yang dapat berpengaruh pada penurunan tekanan darah (Zainur Ridla, 2023).…”
Section: Pembahasanunclassified